Influence of Manufacturing Process on the Microstructure, Stability, and Sensorial Properties of a Topical Ointment Formulation - Pui Shan Chow; Ron Tau Yee Lim; Febin Cyriac; Jaymin C. Shah; Abu Zayed Md Badruddoza; Thean Yeoh; Chetan Kantilal Yagnik; Xin Yi Tee; Annie Bao Hua Wong; Vernissa Dilys Chia; Guan Wang (MDPI AG, 2023)
The manufacturing process for ointments typically involves a series of heating, cooling, and mixing steps. Precise control of the level of mixing through homogenization and the cooling rate, as well as temperature at different stages, is important in delivering ointments with the desired quality attributes, stability, and performance. In this work, we investigated the influence of typical plant processing conditions on the microstructure, stability, and sensorial properties of a model ointment system through a Design of Experiments (DoE) approach. Homogenization speed at the cooling stage after the addition of the solvent (propylene glycol, PG) was found to be the critical processing parameter that affects stability and the rheological and sensorial properties of the ointment. A lower PG addition temperature was also found to be beneficial. The stabilization of the ointment at a lower PG addition temperature was hypothesized to be due to more effective encapsulation by crystallizing mono- and diglycerides at the lower temperature. The in vitro release profiles were found to be not influenced by the processing parameters, suggesting that for the ointment platform studied, processing affects the microstructure, but the effects do not translate into the release profile, a key performance indicator. Our systematic study represents a Quality-by-Design (QbD) approach to the design of a robust manufacturing process for delivering stable ointments with the desired performance attributes and properties.